Cytology in Systematics of Tribe Dobineae (Anacardiaceae) - Khosla, P. K. (Indian Forester, 1973)
Dobineae, a small tribe of Anacardiaceae, with 2 genera namely Dobinea Buch. Ham, ex D. Don and Campylopetalum Forman is distributed in the Sikkim Himalaya and Yunnan and Thailand respectively. The consistency of diploid chromosome complement of 14 in both the genera. is a cytological evidence to revive family status, Podaceae Baillon ex Franchet, for the tribe.